1990
DOI: 10.1111/j.1151-2916.1990.tb07628.x
|View full text |Cite
|
Sign up to set email alerts
|

Phase Equilibria in the Systems SrO‐CuO and SrO‐1/2Bi2O3

Abstract: The phase equilibria of the systems SrO-CuO and SrO-'hBi2O3 were studied by X-ray diffraction analysis of quenched powder samples. The compounds SrCuOz and SrzCu03 melt incongruently at 1085" and 1225"C, respectively. The newly found compound Sr6Biz09 decomposes at 965°C into SrO and Sr3Bi206; Sr3Biz06 melts incongruently into SrO and liquid at 1210°C. SrBi204 undergoes a phase transition at =825"C, and although both are nonstoichiometric, the low-temperature phase is slightly poorer in SrO with 33.5 mol% SrO … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
0

Year Published

1998
1998
2018
2018

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(52 citation statements)
references
References 7 publications
4
48
0
Order By: Relevance
“…[ [15][16][17][18][19][20] The SrCu 2 O 2 phase was not found in the present study as a consequence of the lack of stability of this phase in air. [20,23] The high-pressure phases SrCu 2 O 3 and Sr 2 Cu 3 O 5 [24] were not formed either.…”
Section: Sro-cuomentioning
confidence: 46%
See 1 more Smart Citation
“…[ [15][16][17][18][19][20] The SrCu 2 O 2 phase was not found in the present study as a consequence of the lack of stability of this phase in air. [20,23] The high-pressure phases SrCu 2 O 3 and Sr 2 Cu 3 O 5 [24] were not formed either.…”
Section: Sro-cuomentioning
confidence: 46%
“…[14] Several studies [15][16][17][18][19][20] have been devoted to the SrO-CuO system, in which three phases are known to be stable at 800°C in air: Sr 2 CuO 3 (orthorhombic, space group Immm [21] ), SrCuO 2 (orthorhombic, space group Cmcm [21] ) and Sr 14 Cu 24 O 41 , which is sometimes described as Sr 3 Cu 5 O 8 (orthorhombic, space group Fmmm [22] ). Under conditions of lower oxygen partial pressure, an additional binary oxide with SrCu 2 O 2 composition was observed.…”
Section: Previous Workmentioning
confidence: 99%
“…For instance, the phase diagrams due to Liang et.al. 17 and Wong et al 18 show the position of the peritectic point at 14 : 24, whereas, Solbodin et al 16 and Hwang et al 15 reported the composition to be 3 : 7. It is worth pointing out here that while the liquidus lines in the phase In previous work dealing with the TSFZ growth of undoped SrCuO 2 crystals, use of three different solvent compositions has been reported.…”
Section: Crystal Growthmentioning
confidence: 99%
“…The solvent composition for the undoped compound was taken to be SrO : CuO = 3 : 7 (henceforth, unless mentioned otherwise, the ratio in the context of solvent composition stands for molar ratio SrO : CuO) in accordance with the phase diagram in reference. 15,16 In the growth of doped compounds, the corresponding amount of dopant was added to the solvent disk so that the doping level in the growing crystal remains equal to that in the feed rod. For example, in the growth of SrCu 0.99 Co 0.01 O 2 , the composition of the solvent used was SrO : CuO : CoO = 3 : 6.93 : 0.07.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation